Add: 4x2y, - 3xy2, -5xy2, 5x2y

4x2y, – 3xy2, –5xy2, 5x2y

Answer

On combining the like terms and adding them we get

= 4x2y + (-3xy2) + (-5xy2) + 5x2y

= 4x2y + 5x2y – 3xy2 – 5xy2

= x2y (4 + 5) + xy(-3 – 5)

= x2y (9) + xy2 (- 8)

= 9x2y – 8xy2

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question